Fluvial morphology and sediment transport of the Malekhu Khola, Central Nepal Lesser Himalaya - Tamang, Niraj Bal; Tamrakar, Naresh Kazi; Magar, Milan; Raut, Mahesh (Bulletin of the Department of Geology, 2017)
Areas near the rivers and streams have been widely used for settlement, development works and agriculture due to availability of the resources such as water, aggregates and comparatively easier terrain. It is very important to understand prevailing fluvial conditions for sustainable output. The fluvial conditions of the Malekhu Watershed including the river characteristics, sediment transport and sediment dynamics were studied. Ten river transects and the corresponding segments of the Malekhu Khola were surveyed for cross-sections and longitudinal profiles. Samples were collected in each of the transects and were analysed for suspended sediment concentration. The riverbed sampling was made using Wolman’s pebble count for establishing grain size distribution. Manning’s roughness coefficients were determined to estimate discharge. The study shows that the Malekhu Khola is a sixth order stream. It has been classified into A4-, B4- and C4-type streams. The hypsometric analysis of the Malekhu Watershed shows that it is in mature stage of erosion. Sediment grain size slightly increases downstream but sorting remains extremely poor to moderately poor. The Malekhu Khola shows eroding tendency at 1.2 km, 16.6 km and 20 km from the origin and brings larger particles only during high flow period at the remaining transects. Mean Suspended Sediment Concentrations (SSC) for the Malekhu Khola was 72.14 mg/L, and it increases with increasing discharge and increasing watershed area and is related to velocity of the river, mining activities and local tributaries. Bulletin of the Department of Geology, Vol. 18, 2015, pp. 35-48